P‐85: Spatial‐Resolution‐Improved Light‐Field Imaging System Using Virtual‐Moving Microlens Array without Decrease of Angular Resolution. Issue 1 (29th May 2019) - Lee, Tae-Hyun; Lim, Duck-Kyu; Park, Min-Kyu; Joo, Kyung-II; Kim, Hak-Rin
Abstract : We propose resolution‐enhanced light‐field (LF) imaging system utilizing the virtual‐moving microlens array (MLA). According to the polarization direction of the incident ray, the virtual‐moving MLA can shift sampling positions without physical movement. In our LF imaging system, the spatial‐resolution of the reconstructed images using virtual moving MLA was improved by four times while maintaining angular resolution compared with that obtained with conventional LF imaging system. The real‐time imaging capturing at video frame rate can be implemented by using fast switching polarization control layer.